Efeitos protetores da angiotensina-(1-7) em modelos experimentais de infecção pulmonar - Eliza Mathias Melo (2021)
Failure to resolve exacerbated inflammation triggered by the Influenza A virus (IAV) prevents the return of pulmonary homeostasis and survival, especially when associated with secondary pneumococcal infection. Therapeutic strategies based on pro-resolution molecules have great potential against acute inflammatory diseases. Angiotensin-(1-7) [Ang-(1-7)] is a pro-resolving mediator that acts on its Mas-receptor (MasR) to promote resolution of inflammation. We investigated the effects of Ang-(1- 7) and the role of MasR in the context of IAV infection, post-influenza pneumococcal infection, and moderate and severe pneumococcal infection, assessing lung inflammation, viral and bacterial loads, and lung damage. Therapeutic treatment with Ang-(1-7) decreased neutrophil recruitment, lung injury, viral load and morbidity after a primary IAV infection. Ang-(1-7) induced neutrophil apoptosis and epherocytosis of these cells by alveolar macrophages, but had no direct effect on IAV replication in vitro. Mice deficient in MasR (MasR-/-) were highly susceptible to IAV infection, exhibiting uncontrolled inflammation, increased viral load and higher fatality rate compared to WT animals. Ang-(1-7) was not protective in MasR-/- mice. Interestingly, Ang-(1-7) given during a sublethal dose of IAV infection greatly reduced the morbidity associated with a subsequent S. pneumoniae infection, as seen by the decrease in the magnitude of neutrophil influx, number of bacteria in the blood leading to a lower lethality. This treatment also reduced morbidity of animals infected with S. pneumoniae by reducing bacterial load in the BALF and blood, neutrophil influx, and increased survival when associated with ceftriaxone antibiotic. These results show that Ang-(1-7) protects IAV single-infection, post-influenza pneumococcal infection, moderate pneumococcal infection, and when associated with ceftriaxone promotes survival. Effects seen in IAV infection are dependent on MasR. Mediators of inflammation resolution, such as Ang- (1-7), should be considered for the treatment of viral and bacterial pulmonary infections.